Micro-scale deterministic asperity contact FEM simulation - Kolli, Vasu; Winkler, Andreas; Wartzack, Sandro; Marian, Max (Surface Topography: Metrology and Properties, 2022)
There are numerous stochastic approaches to indirectly couple solid asperity contact with the fluid hydrodynamics in the region of boundary or mixed lubrication. In contrast, deterministic approaches for calculating solid contact pressure curves offer advantages in terms of flexibility and accuracy. This contribution aims at providing a publicly available, automated method to derive solid asperity contact pressure curves for given surfaces, implemented in commercial software based upon Finite Element Method (FEM). Solid asperity pressure curves were calculated and compared to various established stochastic models for artificially generated surfaces and surfaces measured via laser scanning microscopy. Thereby, it was shown that the usage of artificially generated surfaces based on stochastic parameters only allowed an approximate representation of real measured surfaces as well as to lower calculated pressures, so that 3D measurement data is preferred to calculate the contact pressure. Moreover, the values of the FEM model were in a similar region but slightly below the stochastic models over a wide range of gap distances and the asperity pressure graphs were more curved/convex. At very small gap height values, the pressure in the FEM model reached values similar to the stochastic models. This was attributed to the fact that real surface topographies were considered, also allowing for peak-to-valley pairings instead of merely asperity-to-asperity contacts, as well as to the fact that the roughness and mean planes were re-calculated in each simulation step, while most stochastic approaches neglect the elastic deformation of asperities when determining the distances between the rough surfaces.
Keywords: multiscale modeling; finite element method; solid contact pressure; contact mechanics; tribology